(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Predicting and assessing the risk of dental caries in children is a pressing issue in modern paediatric dentistry worldwide, including in Uzbekistan. Significant progress has been made in the prevention of a number of diseases, and the aetiology and pathogenesis of virtually all dental diseases have been well studied. However, even in developed countries such as the United States, Japan and Western Europe, the prevalence of caries in permanent teeth remains at 50% [3,6].